Congo facing a third War? Possible repercussions of the Gatumba massacre - Denis Michael Tull (Stiftung Wissenschaft und Politik (SWP), 2004)
A massacre of Congolese Tutsis at Gatumba refugee camp threatens to disrupt the regional peace process. The refugees, 163 Banyamulenge from South Kivu, were murdered on August 13 at the Gatumba camp in Burundi, close to the Congolese border. Responsibility for the killings was claimed by the Burundian FNL, the only rebel organization still boycotting the Burundi peace process. Paradoxically, the brutal massacre will probably represent only a limited risk to the relatively advanced political transition in Burundi, but a much greater danger for the neighboring state of the Democratic Republic of Congo, which the massacre has brought to the verge of its third war in less than a decade. (SWP-Comments / SWP)
Keywords: 320